Implementasi Model Pembelajaran Cooperative Script Berbantuan Mind Mapping Terhadap Kemampuan Berpikir Kreatif Dan Hasil Belajar Kognitif Siswa Pada Konsep Ekosistem Di Kelas VII SMPN 3 Baregbeg - Yana, Yana; Hindriana, Anna Fitri; Nur, Sofyan Hasanuddin (Edubiologica, 2021)
Reality on the ground, not a few teachers who pay less attention to student involvement in the learning process. In addition, learning models and aids as a means of supporting learning success are underutilized. Therefore in the learning process it is very important to use suitable learning models and aids. The method used in this research is quasi-experimental research (quasi-experiment research). The research design used was a pretest posttest control group. This research was conducted in class VII SMP 2 semester 2018/2019 school year, with a sample of two classes. The results showed that: (1) The teacher's activities in the experimental class which implemented a mind mapping cooperative learning model assisted with mind mapping by 94%, meaning that the teacher implemented the mind mapping assisted cooperative learning model almost entirely achieved in learning, (2) There were significant differences between creative thinking of students in the ecosystem material in the experimental class that the learning process is implemented cooperative script learning model assisted with mind mapping with students in the control class whose learning process uses the STAD learning model, (3) There is a significant difference in the cognitive learning outcomes of students in the ecosystem material in the class experiments with learning processes implemented cooperative script learning models assisted with mind mapping with students in the control class whose learning process uses the STAD learning model, (4) student responses to implemented sikan cooperative script learning model assisted with mind mapping of 79.80%, meaning that it was responded by agreeing with the experimental class students.